Comprehensive Spatial Profile of the Orphan G Protein Coupled Receptor GPRC5B Expression in Mouse Brain - Fu, Wenqi; Franchini, Luca; Orlandi, Cesare (Frontiers in Neuroscience, 2022)
Orphan G Protein Coupled Receptors (GPCRs) are GPCRs whose endogenous ligands are unknown or still debated. Due to the lack of pharmacological modulators, the physiological function of orphan GPCRs is understudied. However, relevant physiological roles associated with orphan GPCRs have been revealed by analysis of animal models and genome wide association studies illuminating an untapped potential for drug discovery. G Protein Coupled Receptor class C Group 5 Member B (GPRC5B) is among the most expressed GPCRs in the central nervous system. Thus, the expression profiling of GPRC5B is an essential step toward understanding GPRC5B function in health and disease. In this study, we generated new GPRC5B polyclonal antibodies and investigated the expression levels of GPRC5B across different organs and brain regions. We identified high levels of GPRC5B glycosylation both in transfected cells and in mouse brain. Moreover, in situ hybridization imaging analysis indicated that Gprc5b was expressed at the highest level in olfactory bulb, hippocampus, cerebellum, and pons. To dissect expression within various neuronal populations, we conducted a comprehensive spatial profiling of Gprc5b across excitatory and inhibitory neuronal types in medial prefrontal cortex, motor cortex, hippocampal regions, hypothalamus, and cerebellum. Overall, we discovered that GABAergic neurons displayed higher Gprc5b expression levels than glutamatergic neurons in most of the analyzed regions with the important exception of the hippocampal dentate gyrus. Overall, the expression analysis of GPRC5B in mouse brain will guide functional studies ultimately positioning GPRC5B in pathophysiological mechanisms and drug discovery.